2021
DOI: 10.1177/02762366211017421
|View full text |Cite
|
Sign up to set email alerts
|

Dreaming About One’s Own Children: An Online Survey

Abstract: Social interactions with close persons are very important and one would expect – according to the continuity hypothesis of dreaming – that the dreamer's own children would show up in dreams quite frequently. So far the extent to which dreams include the dreamer’s own children has not been studied systematically. Overall, 1695 persons (960 women, 735 men; age mean: 53.84 ± 13.99 years) completed an online survey that included questions about dreams and waking-life experiences with their children. The findings i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…Similar to Hall and Van de Castle (1966) and the dream series depicted in Table 1, we found that mothers occurred more often in dreams than fathers—perfectly reflecting the literature demonstrating that the mother is more often described as primary caregiver (Hartnett et al, 2018) and young adults have more contact with their mothers compared with their fathers (Fingerman et al, 2016). One study (Schredl et al, 2021) showed that fathers, on the other hand, also dream less often about their children than mothers do. As parents occurred more frequent in the dreams than siblings, it would be interesting to investigate whether this difference is also reflecting waking-life social patterns, that is, that young adults have more intense relationships with their parents than with their sibling(s).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar to Hall and Van de Castle (1966) and the dream series depicted in Table 1, we found that mothers occurred more often in dreams than fathers—perfectly reflecting the literature demonstrating that the mother is more often described as primary caregiver (Hartnett et al, 2018) and young adults have more contact with their mothers compared with their fathers (Fingerman et al, 2016). One study (Schredl et al, 2021) showed that fathers, on the other hand, also dream less often about their children than mothers do. As parents occurred more frequent in the dreams than siblings, it would be interesting to investigate whether this difference is also reflecting waking-life social patterns, that is, that young adults have more intense relationships with their parents than with their sibling(s).…”
Section: Discussionmentioning
confidence: 99%
“…This fits with the findings, that young adults have more contact with their mother than with the father (Fingerman et al, 2016) and the mother is more often described as primary caregiver (Hartnett et al, 2018). Interestingly, fathers also dream less often about their children than mothers (Schredl et al, 2021). Female family members are more intensely engaged in maintaining contact within the family (Lee et al, 1993); this is reflected in the higher percentage of dreams including parents in female students compared with male students (Table 1).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Even in the area of mobile phones, many individuals use clocks, e.g., in the sample ( N = 3084) of Montag et al [ 3 ], 45% of the participants regularly wore a wristwatch and 67% had an alarm clock for waking up in the morning. According to the continuity hypothesis of dreaming [ 4 , 5 ], we dream about topics that are important to us, e.g., family members [ 6 ], spouses [ 7 ], sexuality [ 8 ], our own children [ 9 ], pets [ 10 ] and work [ 11 ]. Given that punctuality and timekeeping is important (see above), the question arises as to how often clocks for measuring time occur in dreams.…”
Section: Introductionmentioning
confidence: 99%